2018
DOI: 10.22603/ssrr.2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that impaired motor conduction in the bilateral ulnar and tibial nerves underlies cervical spondylotic amyotrophy in patients with unilateral deltoid muscle atrophy

Abstract: Abstract:Introduction: The clinical entity of cervical spondylotic amyotrophy (CSA) is characterized by severe muscle atrophy in the upper extremities with insignificant sensory deficits in patients with cervical spondylosis. However, the pathogenesis of CSA is still unclear.Methods: We assessed electrophysiological motor conduction through the corticospinal tract and ulnar and tibial nerves, which do not supply the deltoid or biceps muscles, of 18 patients with CSA, 12 patients with compressive cervical myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…With the deepening of clinical and imaging technology cooperation and the study of many cases, many scholars have found that high signal does not necessarily indicate a poor prognosis. [17,[35][36][37][38][39] It is proposed that patients with high signal after surgery are better than those with low signal or no signal, and some scholars have found that whether there is high signal before surgery is not directly related to the degree of spinal cord compression or the efficacy of surgery. Some cases of hyperintensity can have reversible changes and have a good prognosis [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…With the deepening of clinical and imaging technology cooperation and the study of many cases, many scholars have found that high signal does not necessarily indicate a poor prognosis. [17,[35][36][37][38][39] It is proposed that patients with high signal after surgery are better than those with low signal or no signal, and some scholars have found that whether there is high signal before surgery is not directly related to the degree of spinal cord compression or the efficacy of surgery. Some cases of hyperintensity can have reversible changes and have a good prognosis [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…MEP measurements were performed in a manner similar to previous reports 8–10 . MEP measurements were performed when the participants were awake.…”
Section: Methodsmentioning
confidence: 99%
“…MEP measurements were performed in a manner similar to previous reports. [8][9][10] MEP measurements were performed when the participants were awake. Surface recording electrodes were placed on the bilateral abductor digiti minimi (ADM) and abductor hallucis (AH) muscles.…”
Section: Mep Measurementsmentioning
confidence: 99%
See 1 more Smart Citation